Water quality: the missing dimension of water in the water–energy–food nexus. Issue 5 (4th April 2021) - Heal, K. V.; Bartosova, A.; Hipsey, M. R.; Chen, X.; Buytaert, W.; Li, H.-Y.; McGrane, S. J.; Gupta, A. B.; Cudennec, C.
ABSTRACT: The role of water quality, particularly its impact on health, environment and wider well-being, are rarely acknowledged in the water–energy–food (WEF) nexus. Here we demonstrate the necessity to include water quality within the water dimension of the WEF nexus to address complex and multi-disciplinary challenges facing humanity. Firstly, we demonstrate the impact of water quality on the energy and food dimensions of the WEF nexus and vice versa at multiple scales, from households to cities, regions and transboundary basins. Secondly, we use examples to demonstrate how including water quality would have augmented and improved the WEF analysis and its application. Finally, we encourage hydrological scientists to promote relevant water quality research as addressing WEF nexus challenges. To make tangible progress, we propose that analysis of water quality interactions focuses initially on WEF nexus "hotspots, " such as cities, semi-arid areas, and areas dependent on groundwater or climate change-threatened meltwater.